Enhanced Photonic Spin Hall Effect Due to Surface Plasmon Resonance - Xinxing Zhou; Xiaohui Ling (IEEE Photonics Journal, 2016)
In this paper, by considering the surface plasmon resonance (SPR) effect, we theoretically study the photonic spin Hall effect (SHE) in a three-layer structure composed of glass, metal, and air. It is revealed that the obtained spin-dependent splitting in photonic SHE is far greater than the previously reported results in refraction when the incident angle is near the resonant angle. The inherent physics behind this interesting phenomenon is attributed to the sharp decrease in Fresnel reflective coefficients around the SPR. We also find that there exists an optimal thickness for minimal resonant reflection, above which the huge beam displacement is also observed. These findings provide us a pathway for modulating the photonic SHE and open the possibility of developing nanophotonic applications such as the SPR-based sensor.